Kesempurnaan Akhlak Dan Pribadi Nabi Muhammad Rasulullah Sallallahu’alaihi Wasallam - Ratih Kumalasari; Sri Mei Ulfani; Ayu Lestari; Dinda Putri Hasanah; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2024)
The Prophet Muhammad was a complete human figure in terms of his humanity and spirituality. The Islamic morals of the Prophet Muhammad are important to practice because they can convey a more essential understanding of Islam because the Prophet Muhammad is an ideal representation of Islam. This research uses qualitative research methods with a library research approach. Qualitative research focuses on a variety of methods, including interpretive and naturalist approaches to the subject of study. The aim of this research is to study the Prophet Muhammad SAW in the Al-Qur'an and increase enthusiasm in emulating the morals of the Prophet Muhammad SAW which are still low among Muslims because they are considered very difficult to use as a guide. The results of this research discuss the morals of the Prophet Muhammad and the perfection of the Prophet Muhammad SAW. In Hadith. The Prophet's honesty, the Prophet's gentleness towards sinners, the Prophet's love for children, the poor and his people, the Prophet's never patient nature, the Prophet's forgiving nature towards people who hated and were hostile to him, the Prophet's democratic nature, the Prophet's humility, the Prophet's generosity, the Prophet's leadership, the Prophet always honored guests, the Prophet's face was always radiant. This research confirms the Islamic morals of the Prophet Muhammad SAW. Aisyah said that the Prophet's morals were the Koran